2012
DOI: 10.4021/cr121w
|View full text |Cite
|
Sign up to set email alerts
|

Treating Refractory Cardiogenic Shock With the TandemHeart and Impella Devices: A Single Center Experience

Abstract: BackgroundPatients with cardiogenic shock (CS) are routinely treated with intra-aortic balloon pumps (IABPs). The utility of 2 new percutaneous left ventricular assist devices (PLVADs), the Impella and TandemHeart, is unknown. The objective of this study was to describe the use of PLVADs for patients with CS at our institution.MethodsAll cases involving PLVADs in patients with CS between between January 1, 2008 and June 30, 2010 at a private, tertiary referral hospital were reviewed retrospectively.ResultsAll … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 17 publications
0
26
1
Order By: Relevance
“…In the controlled observational studies, the 30‐day rates of all‐cause mortality were higher in the Impella arm than in the IABP arm in 2 of the 3 studies that reported this endpoint (Table ) . However, neither reached statistical significance due to their modest sample sizes.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…In the controlled observational studies, the 30‐day rates of all‐cause mortality were higher in the Impella arm than in the IABP arm in 2 of the 3 studies that reported this endpoint (Table ) . However, neither reached statistical significance due to their modest sample sizes.…”
Section: Resultsmentioning
confidence: 96%
“…These outcomes were also examined in one controlled observational study (Table ). Schwartz et al reported lower 30‐day rates of MACE and MI for Impella patients than in IABP patients. However, with a sample size of only 18 patients (13 patients and 5 IABP), no definitive conclusions can be drawn from these data.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Extracorporeal membrane oxygenation (ECMO) provides more extensive circulatory support but it is associated with high rates of peri‐procedural adverse events . Left ventricular assist devices (LVADs) also have their place in the treatment of cardiac disease; however, they require invasive surgical procedures for their implantation, take longer to deploy, are associated with high complication rates, and often damage the heart muscle . No study has yet demonstrated that LVAD therapy is cost‐effective based on conventional definitions of willingness‐to‐pay criteria .…”
Section: Introductionmentioning
confidence: 99%